2008
DOI: 10.1161/strokeaha.107.503870
|View full text |Cite
|
Sign up to set email alerts
|

Sonothrombolysis With Transcranial Color-Coded Sonography and Recombinant Tissue-Type Plasminogen Activator in Acute Middle Cerebral Artery Main Stem Occlusion

Abstract: Background and Purpose-Sonothrombolysis is a new treatment approach in acute ischemic stroke. The results of a monocenter, randomized clinical study are presented. Methods-Subjects with acute middle cerebral artery main stem occlusion were randomized into a target group receiving 1-hour transcranial continuous insonation using a 1.8-MHz Doppler ultrasound (US) probe or a control group. All underwent standard thrombolysis with intravenous recombinant tissue-type plasminogen activator. Results-Thirty-seven subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
3
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(154 citation statements)
references
References 31 publications
3
144
3
4
Order By: Relevance
“…In the CLOTBUST trial (using Doppler), no difference in the rate of symptomatic hemorrhage was detected between ultrasound treated and control patients (Alexandrov et al, 2004). Eggers et al (2008) (TCCS) found a trend toward an increased rate of symptomatic bleeding. Molina et al (2006) (Doppler), who added the contrast agent Levovist to the treatment protocol, and Perren et al (2008) (TCCS with SonoVue) did not detect differences in the incidence of intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the CLOTBUST trial (using Doppler), no difference in the rate of symptomatic hemorrhage was detected between ultrasound treated and control patients (Alexandrov et al, 2004). Eggers et al (2008) (TCCS) found a trend toward an increased rate of symptomatic bleeding. Molina et al (2006) (Doppler), who added the contrast agent Levovist to the treatment protocol, and Perren et al (2008) (TCCS with SonoVue) did not detect differences in the incidence of intracranial hemorrhage.…”
Section: Discussionmentioning
confidence: 98%
“…It provides functional and prognostic information valuable for individual patient management (Allendoerfer et al, 2006;Nedelmann et al, 2009;Perren et al, 2006;Wunderlich et al, 2007). Next to diagnostic applications, randomized clinical studies suggest therapeutic efficacy of ultrasound on recanalization of acute cerebral artery occlusion in terms of an acceleration of fibrinolysis with recombinant tissue-type plasminogen activator (rt-PA) (Alexandrov et al, 2004;Eggers et al, 2008). Echo contrast agents may further improve treatment efficacy (Molina et al, 2006;Perren et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…J. Eggers и соавт. [79] продемонстриро-вали, что добавление к тканевому активатору плазминоге-на ультразвукового воздействия (модификация транскра-ниальной допплерографии) в течение часа увеличивает частоту полной и частичной реканализации с 22,2 до 57,9% (p=0,045).…”
Section: сонотромболизисunclassified
“…Small clinical trials have shown promising results concerning the potential application of ultrasound-enhanced thrombolysis in acute cerebral ischaemia. 28,29 Moreover, the combination of intravenous gaseous microspheres (microbubbles) with ultrasound has been shown to be a potential alternative to recanalise intravascular thrombi. Recently, the first clinical trial has started regarding ultrasound enhanced thrombolysis using microbubbles in patients with acute ST-elevation myocardial infarction.…”
Section: Ultrasound Enhanced Thrombolysismentioning
confidence: 99%